Motivo do uso de suplementos nutricionais por praticantes de atividade física de Antônio Prado - RS - Susin, Sabrina (My University, 2019)
The use of nutritional supplements has become a common practice among gyms, because of users' desire for better aesthetic results. Consumption is amplified by the promises propagated by the mass media. The objective of this study was to verify the reason for the use of nutritional supplements among attendees of academies in the city of Antônio Prado - RS. This is a cross-sectional study. All participants in physical activity attending all the five academies in the city from December 2018 to March 2019 were evaluated. Only participants who used nutritional supplements were excluded, being excluded under the age of 18 years, pregnant women, infants and non-pregnant persons. wanted to participate. Data collection was done through a self-administered questionnaire on different days and shifts to cover all students enrolled. We included 222 participants in physical activity. The majority were women, with a median age of 29 (23-43) years. The most practiced physical activity was bodybuilding (93.2%; n = 207) followed by aerobic exercise (71.6%; n = 159). Whey protein was the most commonly used supplement (40.5%; n = 90). The main reason for the search for supplements was health / well-being with 80.18% (n = 178). Regarding the reason for the use of supplements, the frequency of use of whey protein, maltodextrin, creatine, caffeine, BCAA and hypercaloric was higher, while collagen and omega-3 was lower in those who sought hypertrophy compared to individuals who did not seek. In relation to weight loss, individuals seeking this goal have greater use of whey protein, maltodextrin, caffeine and BCAA. The frequency of use of supplements by health-seeking participants was higher for collagen use and lower for whey protein, creatine, and BCAA when purchased from individuals who did not seek health / well-being. There was a positive correlation between the time of supplement use and physical activity time (r = 0.372, p <0.001), gymnasium attendance (r = 0.201, p <0.009) and income (r = 0.253, p < 0.002). In conclusion, proteins and maltodextrins were the choices of supplements for the reason for the search for hypertrophy and weight loss, while collagen was related to health and well-being. [resumo fornecido pelo autor]
O uso de suplementos nutricionais tornou-se uma prática bastante comum entre os frequentadores de academias de ginástica, em razão do desejo dos usuários em obter melhores resultados estéticos. O consumo é amplificado pelas promessas de propagadas pelos grandes meios de comunicação. O objetivo deste estudo foi verificar o motivo de uso de suplementos nutricionais entre frequentadores de academias da cidade de Antônio Prado - RS. Este estudo é do tipo transversal. Foram avaliados todos os praticantes de atividade física frequentadores de todas as cinco academias da cidade no período de dezembro de 2018 a março de 2019. Foram incluídos apenas participantes que utilizavam suplementos nutricionais, sendo excluídos menores de 18 anos, grávidas, lactantes e pessoas que não quiseram participar. A coleta de dados foi feita através de um questionário autoaplicável em dias e turnos diferentes para que abrangesse todos os alunos matriculados. Foram incluídos 222 participantes de atividade física, sendo a maioria mulheres, com idade mediana de 29 (23-43) anos. A atividade física mais praticada foi a musculação (93,2%; n=207) seguida de aeróbico (71,6%; n=159). O whey protein foi o suplemento mais utilizado pelos participantes (40,5%; n=90). O principal motivo pela busca de suplementos foi a saúde/bem-estar com 80,18% (n=178). Em relação ao motivo do uso de suplementos, a frequência de uso de whey protein, maltodextrina, creatina, cafeína, BCAA e hipercalórico foi maior, enquanto colágeno e ômega-3 foi menor em quem busca por hipertrofia em comparação aos indivíduos que não buscam. Em relação ao emagrecimento, os indivíduos que buscam esse objetivo têm maior uso de whey protein, maltodextrina, cafeína e BCAA. A frequência de uso de suplementos pelos participantes que buscam a saúde/bem-estar foi maior para o uso de colágeno e menor para whey protein, creatina, BCAA, quando comparados aos indivíduos que não buscam por saúde/bem-estar. Houve correlação positiva entre o tempo de uso de suplemento e tempo de atividade física (r=0,372; p<0,001), frequência na academia (r=0,201; p<0,009) e renda (r=0,253; p<0,002). Em conclusão, as proteínas e maltodextrinas foram as escolhas de suplementos para o motivo da busca por hipertrofia e emagrecimento, enquanto o colágeno foi relacionado a saúde e bem-estar. [resumo fornecido pelo autor]
Keywords: Suplementos nutricionais; Academias de ginástica; Exercícios físicos